2019
DOI: 10.15252/emmm.201810201
|View full text |Cite
|
Sign up to set email alerts
|

Impaired telomere integrity and rRNA biogenesis in PARN‐deficient patients and knock‐out models

Abstract: PARN, poly(A)‐specific ribonuclease, regulates the turnover of mRNAs and the maturation and stabilization of the h TR RNA component of telomerase. Biallelic PARN mutations were associated with Høyeraal–Hreidarsson (HH) syndrome, a rare telomere biology disorder that, because of its severity, is likely not exclusively due to h TR down‐regulation. Whether PARN deficiency was affecting the expression of telomere‐related genes was still unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…More recently, it was found that PARN directly trims rRNA precursors and that RNAi depletion of PARN causes their accumulation (Montellese et al, ). In addition, while this manuscript was in revision, Benyelles et al () reported accumulation of 18S pre‐rRNAs in samples derived from HH individuals, as we do here in our proband (Figure d–f), and in a cell line with biallelic PARN knockout. Interestingly, we observed that neither cells with a knockout of a single allele (Figure g) nor individuals heterozygous for pathogenic PARN variants (Figure d–f) had an accumulation of 18S pre‐rRNA, suggesting a dose‐dependent effect.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…More recently, it was found that PARN directly trims rRNA precursors and that RNAi depletion of PARN causes their accumulation (Montellese et al, ). In addition, while this manuscript was in revision, Benyelles et al () reported accumulation of 18S pre‐rRNAs in samples derived from HH individuals, as we do here in our proband (Figure d–f), and in a cell line with biallelic PARN knockout. Interestingly, we observed that neither cells with a knockout of a single allele (Figure g) nor individuals heterozygous for pathogenic PARN variants (Figure d–f) had an accumulation of 18S pre‐rRNA, suggesting a dose‐dependent effect.…”
Section: Discussionsupporting
confidence: 73%
“…Nonetheless, telomeres shortened. It is possible that monoallelic loss of PARN causes telomere shortening through an RNA other than hTR in HCT116 cells, such as that encoding TPP1, as observed in PARN‐deficient HT1080 cells (Benyelles et al, ) or that increased hTR adenylation is sufficient to shorten telomeres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mutation is located in the β‐fold region of PARN (Figure 3A), predicted to lead to the loss of a hydrogen bond in the protein structure and is highly conserved in all 14 species (Figure 3B,F). The pathogenicity of the biallele mutation at this locus has been demonstrated in a Hoyeraal‐Hreidarsson patient reported by Benyelles 23 . Considering P1 also showed the manifestations of Hoyeraal‐Hreidarsson syndrome, we performed direct sequencing of the full PARN coding sequence in P1 and his parents.…”
Section: Resultsmentioning
confidence: 99%
“…While the investigated patient cells also show genome-wide damage, this damage is apparently tolerable when telomeres are sufficiently long and in itself does not cause a significant cell growth defects. Dyskerin, PARN and TCAB1/WRAP53β are involved in various pathways other than telomerase action, such as rRNA modification and biogenesis, mRNA stability, DDR and scaRNAs trafficking to the Cajal bodies ( 46–48 ). In the context of TBD, however, point mutations in these genes are all associated with the common phenotype of reduced telomerase action.…”
Section: Discussionmentioning
confidence: 99%